PENCEGAHAN PERKAWINAN DI BAWAH UMUR DENGAN BIMBINGAN PERKAWINAN STUDI KASUS DI KANTOR URUSAN AGAMA KECAMATAN NOGOSARI TAHUN 2020-2023 (PREVENTION OF UNDERAGE MARRIAGE WITH MARRIAGE GUIDANCE CASE STUDY IN THE NOGOSARI SUB DISTRICT KUA 2020-2023 - Sudalno, S; Sugiyat, S; Hidayat, Muhammad Yunan (AL HUKMU: Journal of Islamic Law and Economics, 2025)
Underage marriage is still a complex social problem in Indonesia, including in Nogosari District, Boyolali Regency. This study aims to analyze the role of marriage guidance organized by the Office of Religious Affairs (KUA) in preventing underage marriage. This study uses a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation. The results of the study indicate that low levels of education, cultural factors, and lack of understanding of marriage rules are the main causes of underage marriage. The marriage guidance program implemented by the KUA plays a role in providing an understanding of the rights and obligations of marriage, increasing the mental readiness of prospective brides and grooms, and reducing the number of early marriages. However, there are obstacles in its implementation, such as limited counseling staff and low community participation. Therefore, optimization of marriage guidance and cooperation between the KUA, local governments, and the community is needed to reduce the number of underage marriages.